PENGARUH STOCK SELECTION SKILL, MARKET TIMING ABILITY, FUND AGE, EXPENSE RATIO, DAN FUND SIZE TERHADAP KINERJA REKSADANA 2016-2021 - Santoso, Pramana Ridha; Kaluge, David (Contemporary Studies in Economic, Finance and Banking, 2022)
Mutual fund is a financial product frequently selected by small investors and those who have no sufficient time and skill to calculate risks and profits from their investment. Here investors entrust their money to people in charge of managing the fund in forms of portfolios. The objective of this research is to assess 16 mutual funds, selected through purposive sampling, from 2016 to 2021. The hypotheses were examined using F test and t test. The classical assumption test consists of normality, multicollinearity, and heteroscedasticity tests, performed in EViews. This study finds that stock selection skill and fund age negatively and significantly affect portfolio performance, that market timing ability positively and significantly influences portfolio performance, and that expense ratio and fund size negatively and insignificantly affect portfolio performance.